2014
DOI: 10.1111/jph.12335
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Epidemiology of Three Virus Diseases on Zucchini Squash

Abstract: Zucchini yellow mosaic virus (ZYMV), Papaya ringspot virus – type W (PRSV‐W) and Zucchini lethal chlorosis virus (ZLCV) cause important diseases on zucchini squash crops in Brazil. ZYMV and PRSV‐W belong to the genus Potyvirus and are transmitted by aphids, whereas ZLCV belongs to Tospovirus and is transmitted by the thrips Frankliniella zucchini. These three viruses may occur simultaneously in the field, and the epidemiology of the corresponding diseases may be determined by interactions among viruses, hosts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Kim et al (2010) observed that the symptoms in C. pepo plants doubly infected with ZYMV and CMV in the field were peculiarly similar to those symptoms caused by CMV alone. According to Moreira, Filho and Rezende (2015) mixed virus infections in cucurbits are very common in natural conditions and can present biological and epidemiological variations, resulting in several effects on the infected hosts, as well as distinct levels of virus accumulation in the infected host tissues. In others mixed infections with CMV and species of the Potyvirus genus, CMV was present in low concentrations as assessed by PTA-ELISA; herein, the virus was also detected by RT-PCR (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Kim et al (2010) observed that the symptoms in C. pepo plants doubly infected with ZYMV and CMV in the field were peculiarly similar to those symptoms caused by CMV alone. According to Moreira, Filho and Rezende (2015) mixed virus infections in cucurbits are very common in natural conditions and can present biological and epidemiological variations, resulting in several effects on the infected hosts, as well as distinct levels of virus accumulation in the infected host tissues. In others mixed infections with CMV and species of the Potyvirus genus, CMV was present in low concentrations as assessed by PTA-ELISA; herein, the virus was also detected by RT-PCR (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, CABYV progress over time (expressed as days after planting or fleece removal) was successfully described by the logistic model. This model commonly used to describe the temporal dynamics of plant viruses [16][17][18][19] has three parameters (µ, γ, α) with a biological sense (epidemic precocity, carrying capacity, epidemic speed) that were considered as dependent variables in statistical analyses and data mining. Parameters were uncorrelated.…”
Section: Discussionmentioning
confidence: 99%